Plan for Reinstatement, 1945 (1945)
1945 1939-1945 "Plan for Reinstatement, 1945" [HFR0095], 1945 This pamphlet, published by the Industrial Welfare Society, outlines the training and resettlement plans for service men and women after demobilisation and covers issues such as emotional problems, further education and reinstatement rights.